ole in good government: the quota system in Iraq as a model - Dr.Hind Mohammed Al-Nasser (Tikrit Journal For Political Science, 2024)
Summary: Minorities in many countries of the world, especially the Arab countries and Iraq, suffer from marginalization and lack of representation in the political system, and obstacles are placed in front of their representation. Therefore, it is a problem for the formation of a rational government that is representative of all. Marginalization is a process opposite to representation that prevents individuals from obtaining the necessary power that qualifies them. To obtain their rights, knowing that there is a close relationship between the representation of minorities and the good governance system. Certainly, the greater the representation, the more we reach a rational government that is representative of all, in addition to the lack of consistency and agreement between the text of the constitution and the legislation in force and what is applied in reality, so the texts of these laws must be amended. In a way that all minorities can be represented satisfactorily, Iraq since 2003 has begun policies to highlight a greater role for minorities, and this is what we have witnessed since the 2005 Constitution and subsequent legislation, most of which were trying to give a greater role to minorities.